EFEKTIVITAS PENGGUNAAN FLYER DALAM UPAYA PENINGKATAN KEPESERTAAN BPJS KETENAGAKERJAAN - A.A Gede Asti Suanda; Nyoman Sri Subawa (LPSDI Bina Patria, 2023)
The goal of this qualitative study is to find out how the effectiveness of using flyer in an effort to in crease BPJS Ketenagakerjaan employment membership. This investigation was done at the Office of the Employment BPJS Bali Denpasar, and at the Regional Office of the Employement BPJS Bali Nusa Tenggara Papua. Observation and interviews were employed for the collection of data. Using probability sampling, Denpasar-based traders with the status of prospective employees and social security participants were interviewed. Reduction, presentation, and conclusion are the data analysis methods utilized. This research employs a triangulation of methods and data sources to verify the reliability of the data. According to the findings of this study, the Employment BPJS has a flyer which contains call to action content to attract the attention and interest of potential participants such as taglines, low nominal contributions, lots of benefits provided and inclusions of various kinds of working professions in the informal sector. Therefore, traders have stated that the BPJS Employment Social Security Protection Program is the program they require to protect themselves from the risks of work or death, and they expect to enroll in the program as soon as possible